The off-label use of anakinra in pediatric systemic autoinflammatory diseases - Maniscalco, Valerio (Ther Adv Musculoskelet Dis, 2020)
Interleukin 1 (IL-1), a central mediator of innate immunity, is considered a master cytokine of local and systemic inflammation. IL-1 has emerged as pivotal in the pathogenesis of autoinflammatory diseases (AIDs), and blockade of its pathway has become a crucial target for therapy. Anakinra (ANA), a recombinant IL-1β receptor antagonist, was the first anti-IL-1 agent employed in clinical practice. ANA is currently approved for the treatment of rheumatoid arthritis, systemic juvenile idiopathic arthritis, adult-onset Still’s disease, and cryopyrin-associated autoinflammatory syndrome. It has also been successfully used for off-label treatment of various monogenic, polygenic, or undefined etiology systemic AIDs. This review describes currently available evidence for the off-label use of ANA in pediatric rheumatologic diseases. Specifically, the use of ANA in Kawasaki disease, idiopathic recurrent pericarditis, Behçet disease, monogenic AIDs, undifferentiated AIDs, chronic non-bacterial osteomyelitis, macrophage activation syndrome, and febrile infection-related epilepsy, in terms of its safety and efficacy. In selected pediatric rheumatic disorders, the off-label administration of ANA appears to be effective and safe. In order to control severe and/or relapsing disease, ANA should be considered as a valuable treatment option in children suffering from rare inflammatory diseases. However, currently available data consist of retrospective studies and short case series; thus, randomized controlled trials and larger series with long-term follow up are mandatory to better assess the efficacy and cost effectiveness of ANA in these challenging patients.